2008
DOI: 10.1086/522159
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination against Herpes Zoster and Postherpetic Neuralgia

Abstract: Background. Herpes zoster (HZ) and postherpetic neuralgia (PHN) cause significant morbidity in older adults. The incidence and severity of HZ and PHN increase with age in association with an age-related decline in varicellazoster virus (VZV)-specific cell-mediated immunity (VZV-CMI). VZV vaccines can boost VZV-CMI. Therefore, we tested the hypothesis that VZV vaccination would protect older adults against HZ and PHN.Methods. We enrolled 38,546 adults у60 years of age in a randomized, double-blind, placebo-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
101
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(102 citation statements)
references
References 44 publications
(92 reference statements)
0
101
0
1
Order By: Relevance
“…Post-licensure studies have confirmed the vaccine's safety and efficacy (50,51). Unfortunately, participation in the zoster vaccine program has been low, likely due to cost and failure to recognize the importance of preventing infectious diseases in older adults.…”
Section: Zostavaxmentioning
confidence: 99%
“…Post-licensure studies have confirmed the vaccine's safety and efficacy (50,51). Unfortunately, participation in the zoster vaccine program has been low, likely due to cost and failure to recognize the importance of preventing infectious diseases in older adults.…”
Section: Zostavaxmentioning
confidence: 99%
“…The duration of pain and discomfort among subjects with zoster was shorter in vaccinated candidates compared with placebo recipients 22,152 . The vaccine reduced the incidence of zoster by 51.3% (63.9% in people aged 60-69 years but only 37.6% in people aged ≥70 years).…”
Section: Preventionmentioning
confidence: 90%
“…In the Shingles Prevention Study (SPS), a doubleblind, placebo-controlled trial, 38,546 healthy adults aged ≥60 years (median 69 years) were randomly assigned to receive a single dose of high-potency vOka (14 times greater potency than the varicella vaccine) or placebo 22,151,152 . Two co-primary end points were investigated: the burden of illness owing to zoster (a severity-by-duration measure representing the total pain and discomfort) and the incidence of clinically significant PHN.…”
Section: Preventionmentioning
confidence: 99%
See 2 more Smart Citations